AN APPLICATION OF FUZZY DELPHI TECHNIQUE TO MEASURE EXPERTS CONSENSUS ON COMMUNICATION SKILLS AMONG ENGINEERING GRADUATES - Amarjit, Singh; Zaida, Mustafa; Azrul Fazwan, Kharuddin; Mohd Farid, Atan (2021)
Delphi method is a technique and structured approach used to review and collect opinions of a group of experts, however, has its own weaknesses. The Fuzzy Delphi Method (FDM), derived from a modifications of Delphi method, considered by many researches as more superior in providing evidence of human linguistic (which is the signature of Delphi Technique). In this paper, Fuzzy Delphi Method was used to assess the content of communication skills among engineering graduates. This development phase is a part of a project to develop an engineering employability skill framework in Malaysia. This phase involves the view of 10 experts who are experienced and have deep knowledge in engineering. It is a rigorous statistical analysis to validate the validity of abstract concept of the communication skills. The paper presented the result of the experts‟ view and the appropriateness of Fuzzy Delphi Method as an important tool to provide information about the validity of communication skills content. Experts‟ perceptions have shown incongruity with respect to speak and understand more than one language among engineers. The experts agreed with engineering graduates might be give a clear direction, listen and ask question in their employability skills proficiency.